Effect of dietary nitrate supplementation on thermoregulatory and cardiovascular responses to submaximal cycling in the heat - Kent, G. L.; Dawson, B.; Cox, G. R.; Abbiss, C. R.; Smith, K. J.; Croft, K. D.; Lim, Z. X.; Eastwood, A.; Burke, L. M.; Peeling, P. (European Journal of Applied Physiology, 2018)
Purpose: This study investigated whether reported improvements in blood flow distribution, and the possible related effects on thermoregulation during exercise following supplementation with beetroot juice (BR), a rich source of dietary nitrate (NO3-), are mitigated in the heat. Methods: 12 male endurance-trained cyclists (age 27 ± 6 years, VO2peak 68.6 ± 8.1 ml/kg/min) completed two 60 min submaximal cycling trials at 60% of VO2peak power output. Trials were performed in hot environmental conditions (33.3 ± 0.4 °C, 48.8 ± 3.0% RH) following 3 days of supplementation with either NO3--rich BR (6.5 mmol NO3- for 2 days and 13 mmol NO3- on the final day) or NO3--depleted placebo (PLA). Salivary NO3- and nitrite (NO2-) were measured before and after the supplementation period. During exercise, cutaneous blood flow, blood pressure (MAP), core temperature (Tc), mean skin temperature (Tsk), indices of muscle oxygenation and oxygen (O2) consumption were measured. Results: Salivary NO3- and NO2- increased significantly following BR by 680 and 890%, respectively. There were no significant differences observed for cutaneous blood flow, MAP, Tc, Tsk, muscle oxygenation, or O2 consumption between BR and PLA. Conclusion: This investigation shows that the ergogenic effects and health benefits of BR supplementation, such as augmented cutaneous blood flow, reduced MAP, increased muscle oxygenation, and improved aerobic efficiency may be attenuated when exercise is performed in hot conditions.